Pelaksanaan Program Keselamatan dan Kesehatan Kerja terhadap Tenaga Kesehatan pada Masa Pandemi Covid-19 : (Studi Berdasarkan Undang-Undang Nomor 13 Tahun 2003 di Klinik Anugerah Ibu Mataram) - I Gusti Agung Ayu Widya Prasanti; H. Zaeni Asyhadie (Private Law, 2022)
This study aims to determine the factors and implementation of occupational safety and health programs for health workers during the Covid-19 pandemic based on Law No. 13 of 2003 at the Anugerah Ibu Mataram Clinic. The method used is an empirical normative legal research method. Based on the study results, the Anugerah Ibu Mataram Clinic does not have specific guidelines regarding occupational safety and health programs. However, based on Law Number 13 of 2003, the Anugerah Ibu Mataram Clinic has implemented occupational safety and health regulations, especially during this pandemic, well performed. This occupational safety and health program influenced by several factors, namely juridical factors and non-juridical factors.